Better job skills in 3 easy steps - Field, Ben T. (Delmar/Thomson Learning, 2000)
This practical and concise guide is a must-have for anyone looking for a first job right out of high school or college, reentering the job market, or changing careers. It employs a three-step approach -- compile, analyze, and organize -- that directs readers step-by-step through examples and self-directed activities to assess skills, aptitudes, and interests.